Impact of a collaborative childhood anaemia intervention programme in Peru. Issue 6 (16th March 2021) - Whitney, Rachel; Centrone, Wayne A.; Mamani, Hoover Supo; Falkenstein, Karen; Levine, Robert S.; Harris, Jaden; Hazlitt, Melissa; Lim, Czer Anthoney
Abstract: Objectives: To evaluate the impact of a 12‐month multi‐modal public health intervention programme for treating and preventing anaemia among children aged 6 months to 4 years in an underserved community in Peru. Methods: The intervention included nutritional education, use of a Lucky Iron Fish ® cooking tool, and dietary supplementation. The primary outcome measure was anaemia resolution. Secondary outcomes included absolute changes in haemoglobin, change in knowledge survey scores and adherence to interventions. Chi‐square test and Mann–Whitney U‐test were employed to identify associations between anaemia and intervention‐related measures. Variables found to be significantly associated in bivariate analysis or of clinical importance were included in a logistic regression model. Results: Of the 406 children enrolled, 256 (63.1%) completed the programme. Of those, 34.0% had anaemia at baseline; this decreased to 13.0% over 12 months. The mean haemoglobin for all ages at baseline was 11.3 g/dL (SD 0.9). At 12 months, the mean was 11.9 g/dL (SD 0.8), with a mean increase of 0.5 g/dL (95% CI 0.4–0.6). Children with anaemia at baseline saw an increase of 1.19 g/dL at the 12‐month follow‐up (95% CI 1.12–1.37). Parents correctly answered 79.0% of knowledge assessment questions at baseline, which increased to 86.6% at 12 months. Conclusions: We observed a reduction in the prevalence of mild to moderate anaemia among study participants in this vulnerable population and conclude that multi‐modal intervention programmes providing nutrition education in conjunction with low‐cost iron supplementation and easy‐to‐use Lucky Iron Fish ® cooking tools may reduce and prevent anaemia in children.